Proceedings of 2017 Chinese Intelligent Systems Conference Volume II - Jia, Yingmin; Du, Junping; Zhang, Weicun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents selected research papers from CISC'17, held in MudanJiang, China. The topics covered include Multi-agent system, Evolutionary Computation, Artificial Intelligence, Complex systems, Computation intelligence and soft computing, Intelligent control, Advanced control technology, Robotics and applications, Intelligent information processing, Iterative learning control, Machine Learning, and etc. Engineers and researchers from academia, industry, and government can gain valuable insights into solutions combining ideas from multiple disciplines in the field of intelligent systems. .
Adaptive Tracking Control of A Single-link Flexible Robotic Manipulator System with Unmodeled Dynamics and Motion Constraint -- Spherical Panorama Stitching Based on Feature Matching and Optical Flow -- Research on Gait Recognition and Step Rate Detection Based on SVM and Auto-correlation Analysis -- A Robust Fast Type-2 Fuzzy Induction Control System -- Esophagus Tumor Segmentation Using Fully Convolutional Neural Network and Graph Cut.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Control, Robotics, Automation